Insulin resistance and testosterone level in Indonesian young adult males - Kurniawan Liong Boy; Adnan Endy; Windarwati; Mulyono Budi (Sciendo, 2020)
Introduction. Central obesity is characterized by the accumulation of abdominal fat which may lead to several diseases including insulin resistance. The prevalence of central obesity is higher in male and the incidence in young adult males is increased. Central obesity is also related to low testosterone levels. The research aimed to assess the relationship between the testosterone levels and insulin resistance of young adult males with central obesity.